Enhancing Financial Literacy and Digital Marketing for Garment Business Actors in Sastrodirjan, Dukuh Bleber to Support Local Economic Growth - Firmanadi , M. Arianda Ihza; Ulumudin, Dimas Ihya; Trianasari, Ina; Mahabalillah, Mahabalillah; Putri, Karina Eka (Urecol Journal. Part B: Economics and Business, 2025)
This community service activity focuses on enhancing the financial literacy and digital marketing skills of Micro, Small, and Medium Enterprises (MSMEs) in the garment sector in Sastrodirjan Village, Dukuh Bleber, Wonopringgo District. Many garment MSMEs in this region face challenges in optimal financial management and the utilization of digital technology for market expansion and product promotion. Through a series of interactive training sessions, practical workshops, and personalized mentoring, this program will equip participants with the fundamentals of accounting, working capital management, digital marketing strategies (including social media optimization and e-commerce for fashion products), and appealing garment product photography techniques. It is hoped that this improvement in competence will not only enhance the competitiveness of garment MSMEs but also significantly drive local economic growth and the well-being of the Sastrodirjan Village community in a sustainable manner.